Recovery dynamics of carabid beetles (Coleoptera, Carabidae) in colombian tropical dry forest - Ariza Lozano, Gloria Maria (2021)
In this work, I characterized the dynamics of carabid beetles along an environmental gradient formed by successional processes and a marked dry season in three different habitat types (pasture as initial point, early successional stage, and forest as intermediate successional stage) in a Colombian tropical dry forest landscape. In the first chapter, background context is provided and the scope of the thesis is established. In chapter 2, I analyzed the suitability of morphological traits to infer not only functional response traits but also the adaptability of carabid beetles to the harsh TDF environment exasperate by the El Niño/Southern Oscillation (ENSO). I also compared qualitative and quantitative variables among the El Niño and non-El Niño events to observe possible carabid beetle changes as a result of environmental variability. In chapter 3, I evaluated the response of carabid beetles (both at the assemblage and individual species levels) along TDF succession and dry and wet periods, which was exasperated by the El Niño/Southern Oscillation (ENSO). To better understand these responses, I related environmental variables (soil and air humidity and temperature, leaf litter depth and canopy cover) to the beetle assemblage to identify drivers of successional dynamics. Similarly, and with the goal to have a better understanding of the successional dynamics of these organisms, I explored in chapter 4 the functional response of carabid beetles to succession. I identified ecological groups present in different successional habitat types in TDF, and environmental variables related to each trait. In chapter 5, I present a list of TDF carabid species collected from the Valley of Magdalena River (Colombia), and ecological information associated with these species inferred from morphological traits, in an attempt to offer a starting point for future studies on this taxonomic group. Finally, in chapter 6, I provide a general overview of my thesis to synthesize the findings and propose general patterns of the dynamics of carabid beetles in the TDF successional environment.